If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 7 = 11 Reorder the terms: 7 + a = 11 Solving 7 + a = 11 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + a = 11 + -7 Combine like terms: 7 + -7 = 0 0 + a = 11 + -7 a = 11 + -7 Combine like terms: 11 + -7 = 4 a = 4 Simplifying a = 4
| 16R+4R+80=X | | -2x^4(6x^3-5x+5)= | | 790=7.5x+(197.5+(-1.875x)) | | 9+2(b-8)=9(-3-2b) | | 5p=16-3p | | 6-x+2x=3x | | 3(6y-6)-(2y+7)= | | 1.5=x*11 | | 5e-14=8 | | 4n(-n^3-4n+1)= | | 8-2(2x-5)=6 | | -24+w-8=4 | | 3z-2z=8 | | 3x^2-2x=5x+1 | | 7x^2+5x-16=0 | | -750+150(3)= | | 5x-1=2(x+10) | | 17y-2418=59 | | -750+150(2)= | | -5.6h+72=-30 | | -21=-5x+3x+1 | | 6a(7a^2+8a-5)= | | 35x^2-13x-4=0 | | x*25=10 | | (2y+4)(y+7)=0 | | 3(6x-6)-(2x+7)= | | 4=m | | 5-.33333x=17 | | 2784=(40+2x)(30+2x) | | 5-.3x=17 | | -24+w+7=4 | | 2a^4(-5a^4-9)= |